Chemical Quality of Drinking Water from Community Wells - Adelina Siregar; Johannis P. Haumahu; Elizabeth Kaya; June Putinella; Robby G. Risamasu; Rudy Soplanit (Journal La Lifesci, 2026)
Water is a primary necessity for human life, and its quality directly affects public health and community welfare. In Wayame Village, Ambon City, shallow wells are still used by the community as a source of water for daily needs, including drinking water. This study aimed to evaluate the chemical quality of shallow well water by comparing laboratory test results with the drinking water quality standards established by the Ministry of Health of the Republic of Indonesia. This study employed a descriptive quantitative method. A total of eight shallow well water samples were collected from community wells in Wayame Village using purposive sampling. The chemical parameters analyzed included pH, fluoride, total chromium, cadmium, nitrite, nitrate, iron, hardness, chloride, manganese, lead, and free chlorine. Laboratory analysis was conducted at the Provincial Health Laboratory of Maluku, and the results were compared with the Regulation of the Minister of Health of the Republic of Indonesia Number 492/Menkes/Per/IV/2010. The results showed that most chemical parameters were below the permissible limits for drinking water. Fluoride, total chromium, cadmium, nitrite, nitrate, iron, hardness, chloride, manganese, and lead were within the required standards. However, several samples showed pH values below the minimum standard, indicating slightly acidic water conditions. In addition, free chlorine levels in all samples were below the recommended range, indicating limited residual disinfection capacity.